Meningkatkan Keterampilan Berpikir Kritis dan Kerja Sama Peserta Didik Melalui Model LAMPION pada Muatan IPAS - Rahmawati, Siti Rafika; Jannah, Fathul (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
This study was motivated by the low level of students’ critical thinking and collaboration skills in science, environment, technology, and society (IPAS) learning. The purpose of this research was to enhance students’ critical thinking and collaboration skills through the implementation of the LAMPION model, which combines Problem-Based Learning (PBL), Group Investigation (GI), and Teams Games Tournament (TGT). The study employed Classroom Action Research (CAR) with the Kemmis & McTaggart model, consisting of four stages: planning, action, observation, and reflection, conducted over four meetings. The subjects of this research were 10 fifth-grade students of SD Kristen Banjarmasin. Data were collected through student activity observations, skill assessment rubrics, and learning outcome tests. The findings revealed significant improvements in students’ critical thinking and collaboration skills after the implementation of the LAMPION model. Therefore, the LAMPION model is proven effective and can be recommended as an innovative learning strategy for IPAS instruction in elementary schools.